Meta-Analysis the Effect of Oral and Injection Contraceptives on Breast Cancer - Rahardjo, Setyo Sri; Pamungkasari, Eti Poncorini; Dilma’aarij, Dilma’aarij (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Oral contraceptives and injec